Monitoring the photosynthetic activity at single-cell level in Haematococcus lacustris - Patil, P P; Nagy, K; ÁBrahám, Á; Vass, I; Szabó, M (Photosynthetica, 2023)
Haematococcus lacustris is an important species of green algae because it produces the high-value carotenoid astaxanthin. Astaxanthin production is enhanced by various stress conditions causing the transformation of green vegetative cells to red cells with high amounts of astaxanthin, which plays various photoprotective and antioxidant roles. Although intensive research has been conducted to reveal the regulation of astaxanthin production, the photosynthetic capacity of the various cell forms is unresolved at the single-cell level. In this work, we characterized the photosynthetic and morphological changes of Haematococcus cells, using a combination of microfluidic tools and microscopic chlorophyll fluorescence imaging. We found marked but reversible changes in the variable chlorophyll fluorescence signatures upon the transformation of green cells to red cells, and we propose that the photosynthetic activity as revealed by single-cell chlorophyll fluorescence kinetics serves as a useful phenotypic marker of the different cell forms of Haematococcus.
Keywords: Haematococcus lacustris; photoprotection; photosynthesis; photosystem II; chlorophyll fluorescence